(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This thesis explores the implementation of eco-labels as a creative approach to enhance green marketing strategies within businesses. It examines how eco-labels serve as crucial tools for differentiating environmentally friendly products, fostering consumer trust, and influencing purchasing decisions. The research analyzes the relationship between eco-label effectiveness, consumer awareness, and marketing communication strategies. The findings will contribute to the understanding of eco-labels’ role in promoting green marketing practices.